Algorithms Development in Detection of the Gelatinization Process during Enzymatic âDodolâ Processing - Azman Hamzah; Mohd Marzuki Mustafa; Aini Hussain (LPPM ITB, 2007)
Computer vision systems have found wide application in foods processing industry to perform quality evaluation. The systems enable to replace human inspectors for the evaluation of a variety of quality attributes. This paper describes the implementation of the Fast Fourier Transform and Kalman filtering algorithms to detect the glutinous rice flour slurry (GRFS) gelatinization in an enzymatic âdodol. processing. The onset of the GRFS gelatinization is critical in determining the quality of an enzymatic âdodol.. Combinations of these two algorithms were able to detect the gelatinization of the GRFS. The result shows that the gelatinization of the GRFS was at the time range of 11.75 minutes to 14.75 minutes for 24 batches of processing. This paper will highlight the capability of computer vision using our proposed algorithms in monitoring and controlling of an enzymatic âdodol. processing via image processing technology.